RELATIONSHIP BETWEEN ALBUMIN LEVELS IN TYPE 2 DIABETES MELLITUS PATIENTS : HUBUNGAN KADAR ALBUMIN PADA PENDERITA DIABETES MELITUS TIPE 2 - Yohani, Erni; Evania Melly Fera Mbeo; Previta Zeizar Rahmawati; Ariana Listuhayu Wahyuni (Journal of Nursing Care and Biomolecular, 2025)
Introduction: Diabetes Mellitus is a metabolic disorder characterized by insulin resistance.The state of diabetes affects the metabolism of proteins in the body, one of which is albumin This study aims to determine the relationship between Albumin Levels in Type 2 Diabetes Mellitus Patients at Prasetya Husada Hospital. Methods: quantitative descriptive with a sample of all medical record data as many as 70 patients. Results: relationship between the value of albumin levels and the severity of diabetics Analysis: a significant correlation between albumin levels and the severityof diabetes mellitus, the relationship between these two variables is negative with the degree of relationship that is moderate correlation. (p< 0.00; r = - 0.506). Discussion: The Albumin levels in Diabetes Mellitus sufferers are described based on age, length of diagnosis, and severity, obtaining significant results between the severity of Diabetes Mellitus and the Albumin levels which are correlated or related.